Different functional groups modified porous organic polymers used for low concentration CO2 fixation. Issue 76 (2nd September 2021) - Dai, Zhifeng; Bao, Yuanfei; Yuan, Jindong; Yao, Jinzhong; Xiong, Yubing
Abstract : Different functional groups modified porous organic polymers were constructed for the low concentration (15% v/v) CO2 chemical fixation. Abstract : Through a facile post-synthetic method, different kinds of polar group-functionalized ionic liquid porous organic polymers (POP-PA-COOH, POP-PA-OH, and POP-PA-NH2 ) were obtained. The materials can be used as efficient heterogeneous catalysts in the cycloaddition reaction of CO2 with epoxides under mild and co-catalyst-free conditions. It is demonstrated that POP-PA-NH2 possesses much higher catalytic activity than POP-PA-OH and POP-PA-COOH. Interestingly, this activity difference can further be amplified when the reaction is carried out under low CO2 concentration, and POP-PA-NH2 possesses a conversion of 84.7% with a selectivity of 99.0% in 96 h. It is noteworthy to mention that research focusing on the transformation of CO2 under low concentration using heterogeneous catalysts is rare and still a challenge. The excellent activities of POP-PA-NH2 under low CO2 concentration make this material a good candidate for CO2 elimination under mild conditions.